(untitled) (Analysis in Theory and Applications, 2018)
The objective of this note is to provide some (potentially useful) integral transforms (for example, Euler, Laplace, Whittaker etc.) associated with the generalized k-Bessel function defined by Saiful and Nisar [3]. We have also discussed some other transforms as special cases of our main results.